The Role of Self Concepts on Achieving Motivation in RSBI Students and Regular Students - Lincaria Sutismawati Sirait; Tabitha Lily; Eko Pamuji; Mutjaba M. Momin; Surja Permana (Jurnal Didaskalia, 2018)
Not quarantee RSBI students have good achievement in academic and be success people if they do not have motivation in it. Achievement motivation is one factor to hold academic achievement that can be influenced by student self concept. The purpose of this study was to examine the relation between self concept and achievement motivation. How percentage self concept role emerge achievement motivation. The result of this study is founded significant correlation between self concept and achievement motivation. 13,3% self concept play role in RSBI students’ achievement motivation and 35,4% in Regular students’ achievement motivation. In other, there is differences between RSBI students’ self concept and Regular students’ self concept. Despite there is no differences achievement motivation between RSBI and regular students.